Correlating blocking temperatures with relaxation mechanisms in monometallic single-molecule magnets with high energy barriers (Ueff > 600 K). Issue 49 (8th May 2019) - Giansiracusa, Marcus J.; Kostopoulos, Andreas K.; Collison, David; Winpenny, Richard E. P.; Chilton, Nicholas F.
Abstract : Correlating blocking temperatures with relaxation mechanisms in single-molecule magnets. Abstract : We report an empirical correlation between the blocking temperature of large energy barrier SMMs and the relaxation time at the point where the Raman and Orbach relaxation mechanisms have the same rate; this supports the idea that the ability to retain magnetisation is controlled by the Raman relaxation process in these materials.